Integrated Soft Optoelectronics for Wearable Health Monitoring. Issue 8 (21st June 2020) - Biswas, Shantonu; Shao, Yitian; Hachisu, Taku; Nguyen‐Dang, Tung; Visell, Yon
Abstract: Recent developments in stretchable electronics hold promise to advance wearable technologies for health monitoring. Emerging techniques allow soft materials to serve as substrates and packaging for electronics, enabling devices to comply with and conform to the body, unlike conventional rigid electronics. However, few stretchable electronic devices achieve the high integration densities that are possible using conventional substrates, such as printed rigid or flexible circuit boards. Here, a new manufacturing method is presented for wearable soft health monitoring devices with high integration densities. It is shown how to fabricate soft electronics on rigid carrier substrates using microfabrication techniques in tandem with strain relief features. Together, these make it possible to integrate a large variety of surface mount components in complex stretchable circuits on thin polymer substrates. The method is largely compatible with existing industrial manufacturing processes. The promise of these methods is demonstrated by realizing skin‐interfaced devices for multimodal physiological data capture via multiwavelength optoelectronic sensor arrays comprised of light emitting diodes and phototransistors. The devices provide high signal‐to‐noise ratio measurements of peripheral hemodynamics, illustrating the promise of soft electronics for wearable health monitoring applications. Abstract : Recent developments in emerging stretchable electronics hold promise to advance wearable technologies for health monitoring. Here, skin‐interfaced wearable multiwavelength optoelectronic sensor arrays comprised of light‐emitting devices and phototransistors are realized using a new manufacturing method based on microfabrication techniques on rigid carrier. These highly integrated devices in soft substrates provide high signal‐to‐noise ratio measurements of peripheral hemodynamics, illustrating the promise of this method.